2008
DOI: 10.1016/j.joca.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of cartilage defects in people with knee osteoarthritis

Abstract: Over 2 years, cartilage defects tend to progress in people with symptomatic OA, with only a small percentage decreasing in severity. Increasing age and increased bone area are risk factors for progression. Interventions aimed at preventing cartilage defects from occurring and reducing their severity may result in a reduction in the severity of OA, by reducing loss of articular cartilage and subsequent requirement for knee joint replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
181
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(192 citation statements)
references
References 43 publications
3
181
0
8
Order By: Relevance
“…Early joint structural changes such as cartilage defects, loss of cartilage volume, subchondral bone expansion and bone marrow lesions are present prior to the onset of joint symptoms and clinical OA [18]. Bone expansion in the tibial subchondral area play an initial role in the aetiology of knee cartilage defects and cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early joint structural changes such as cartilage defects, loss of cartilage volume, subchondral bone expansion and bone marrow lesions are present prior to the onset of joint symptoms and clinical OA [18]. Bone expansion in the tibial subchondral area play an initial role in the aetiology of knee cartilage defects and cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
“…These defects tend to progress in symptomatic knee OA. Prevention of cartilage damage or reducing their severity by intervention may retard OA progression [18]. Inadequate levels of serum 25-OHD in patients with knee OA is of major concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have demonstrated that FDs can lead to cartilage degeneration, defect enlargement and tissue volume loss [55][56][57]. In addition, the abnormal strains that occur due to the presence of a FD are likely to make the tissue more susceptible to mechanical injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The serum level of 25-hydroxy vitamin D depends on various parameters such as ultraviolet irradiation (determined by the time of day) to skin, skin pigmentation, season, [5][6][7] latitude, age, dietary habits, gender, obesity, and many others factors. [6][7][8][9] It is known that vitamin D has role in mineralization, demineralization, remodeling, and maintenance of bone. Therefore its deficiency may be implicated in the pathogenesis of osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%